Multi-axial Fatigue of Trabecular Bone with Respect to Normal Walking - Mostakhdemin, Mohammad (Springer, 2015)
This book focuses on the analysis and treatment of osteoporotic bone based on drug administration, tracking fatigue behavior and taking into consideration the mechanical interaction of implants with trabecular bone. Weak trabeculae are one of the most important clinical features that need to be addressed in order to prevent hip joint fractures.